A Single Amino Acid Change in the Murine Leukemia Virus Capsid Gene Responsible for the Fv1(nr) Phenotype - Jung, Yong Tae (American Society for Microbiology, 2000)
The nr allele at the mouse Fv1 restriction locus governs resistance to B-tropic and some N-tropic murine leukemia viruses (MLVs). Sequence analysis and site-specific mutagenesis of N-tropic MLVs identified a single amino acid difference responsible for this restriction that is distinct from the site that governs N or B tropism. Viruses with other substitutions at this site were evaluated for altered replication patterns.